The Effect Of Stress On Student Learning Motivation In The Management Study Program, Faculty Of Economics And Business, Muhammadiyah University Of Makassar - Nurul Asmi; Muh. Nur R; Nurinaya Nurinaya (CV. AFDIFAL MAJU BERKAH, 2025)
The purpose of this study was to determine the Effect of Stress on Learning Motivation of Students in the Management Study Program, Faculty of Economics and Business, Muhammadiyah University of Makassar. The population in this study were all students of the management study program class of 2021 totaling 374 people, using the Slovin calculation with an error rate of 5%, a research sample of 79 people was obtained. The type of research used in this study is quantitative. The data collection method uses a questionnaire. The data analysis techniques used are simple regression analysis, determination test (R2), and t-test (partial) using statistical calculations through the Statistical Package for the Social Science (SPSS) version 24 application. Based on the research that has been conducted, the results of this study indicate that the stress variable has a positive and significant effect on Learning Motivation